Akuntansi sebagai Alat Komunikasi Berkaitan dengan Lingkungan Hidup Studi Kasus pada Aneka Tambang Batubara Bukit Asam Tbk. - Astuti, Tutut Dewi (Akmenika, 2014)
The objective of this research was to understand accounting as a communication tool for company in relationship with the environment. The data collection method used in this research was documentation. The data analysis was used to find out the relationship bet-ween accounting and environment which was carried out by identifying the environmental information on annual reports of PT PT Tambang Batubara Bukit Asam Tbk. The results show it was (1) the environmental information was provided on annual report were other than the financial statement, (2) six groups of environmental information were provided by company, (3) most of the environmental information (near to 78,52%) were provided in qualitative information.